Out-of-Pocket Spending for Deliveries and Newborn Hospitalizations Among the Privately Insured. Issue 1 (January 2022) - Chua, Kao-Ping; Fendrick, A. Mark; Conti, Rena M.; Moniz, Michelle H.
Abstract : (Abstracted from Pediatrics 2021;148(1):e2021050552) Previous studies on the financial burden of childbirth on privately insured families have been focused on the out-of-pocket costs of maternal care, including hospitalization for delivery. However, there are no recent data that has considered the out-of-pocket spending on hospital stays for delivery and neonatal intensive care.